Meniti Sukses Akademis: Peran Fasilitas Sekolah dan Motivasi Prestasi pada Hasil Belajar Mahasiswa - Nugraha, Derry (AL-BAHTS: Jurnal Ilmu Sosial,Politik, dah Hukum, 2023)
This study aims to analyze the effect of school facilities and achievement motivation on the learning outcomes of STKIP PGRI Sukabumi students. Through quantitative descriptive methods, research was conducted on first, third and fifth semester samples using questionnaires given to 100 respondents. The results of data analysis using multiple linear regression showed significant findings. School facilities (X1) had a significant influence on learning outcomes (Y) with a significance value of 0.004 (<0.05) and a calculated t value of 2.953 (> t table 1.984), showing a real influence on learning outcomes. Similarly, achievement motivation (X2) also has a significant effect on learning outcomes (Y) with a significance value of 0.000 (<0.05) and a calculated t value of 6.591 (> t table 1.984), confirming its positive influence on learning outcomes. Simultaneously, school facilities and achievement motivation significantly affect learning outcomes with a significance value of 0.000 (<0.05) and a calculated f value of 53.932 (> f table 3.09), indicating that both play a role in improving student learning outcomes by 52.7%. In conclusion, school facilities and achievement motivation have a strong influence on student learning outcomes.